1990
DOI: 10.1021/jm00163a032
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine receptor binding activity of 8-substituted-9-(3-substituted-benzyl)-6-(dimethylamino)-9H-purines

Abstract: A series of 8-substituted analogues of 9-(3-aminobenzyl)-6-(dimethylamino)-9H-purine (8) were synthesized and tested for their ability to bind to the benzodiazepine receptor (BZR) in rat brain tissue. The most active compound was the 8-bromo-9-(3-formamidobenzyl) analogue 16 (IC50 = 0.011 microM), which was 1000-fold more active than the parent 9-benzyl-6-(dimethylamino)-9H-purine (1) and nearly as active as diazepam. Although substitution of a m-formamido group and an 8-bromo substituent on 1 imparted potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…12,13) The activity is indicated by MEC (minimum effective concentration), which is the concentration of the test compounds required for more than 1 IU/ml induction of IFN. The 6-unsubstituted and 6-substituted purines (2)(3)(4)(5)(6)(7)(8)14) were inactive at the maximum concentration tested (10 mM), while lead compound 1 showed MEC of 10 mM. 6) In conclusion, we have synthesized various 6-substituted 9-benzyl-8-hydroxypurine derivatives and evaluated their IFN-inducing activities.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…12,13) The activity is indicated by MEC (minimum effective concentration), which is the concentration of the test compounds required for more than 1 IU/ml induction of IFN. The 6-unsubstituted and 6-substituted purines (2)(3)(4)(5)(6)(7)(8)14) were inactive at the maximum concentration tested (10 mM), while lead compound 1 showed MEC of 10 mM. 6) In conclusion, we have synthesized various 6-substituted 9-benzyl-8-hydroxypurine derivatives and evaluated their IFN-inducing activities.…”
mentioning
confidence: 94%
“…8-Hydroxypurine derivatives have been reported to have a wide range of biological activities, such as corticotropin-releasing hormone receptor antagonism, 1,2) anti-rhinovirus activity, 3) xanthine oxidase inhibiting activity 4) and excellent binding affinity to a benzodiazepine receptor. 5) Recently, we found a novel type of lead compound, 9-benzyl-8-hydroxyadenine (1), possessing potent interferon (IFN)-inducing activity and conducted substituent modifications at the 2-, 8and 9-positions of 1 to clarify the structure-activity relationships. 6) Consequently, we found that the 8-hydroxyl and 9benzyl groups of 1 are required for the expression of IFN-inducing activity and the introduction of an appropriate alkylchain substituent at the 2-position of 1 remarkably increases the activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The imidazo-[1,2-a]-pyrimidines inhibit binding of [ 3 H] flunitrazepam from rat brain preparations. Series D: This series contains 31 derivatives of 6,9-disubstituted purines with their observed binding affinities to the rat brain tissue (Kelley et al, 1989(Kelley et al, , 1990Saha et al, 1991) as reported in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…These are also useful intermediates for chemical industrial products, and also, purine derivatives are also used as agrochemicals like fungicides, insecticides, and herbicides . In consequence, the synthesis of substituted purine molecules has attracted many researchers, and many strategies have been pursued with catalysts, such as acetic anhydride , ethanesulfonic acid , NaH , FeCl 3 –SiO 2 , PPA , Pd(OAc) 2 –CuI , CsCO 3 , H 2 S/base , H 2 S/S 8 , Pd 2 dba 3 , cellulose sulfuric acid , pyridine , and microwave condition .…”
Section: Introductionmentioning
confidence: 99%